Lived experiences of women with memories of childbirth. (2nd March 2022) - Suzuki, Yumiko; Okubo, Noriko
Abstract : Background: Few studies have explored women's experiences of the memories of childbirth. This study aimed to describe how women recall memories of childbirth in their daily life, in order to improve childbirth and postpartum care. Methods: A descriptive phenomenology was used. Unstructured interviews with six women recruited using snowball sampling were conducted, asking them to reflect on their childbirth memories and the experience of memory recall. Results: In daily life, women did not recall the memories of childbirth often. After childbirth, women focused on living in the present. They had usually forgotten childbirth memories, but sometimes memories were evoked as a source of support or distress, depending on context. Conclusions: Midwives should be cognisant of women's individual circumstances. Their role exceeds that of a medical specialist during the intrapartum period, as they are involved in creating impactful memories. These results also support the significance of long-term care.